Quantifying the uncertainty in simulating global tropospheric composition due to the variability in global emission estimates of Biogenic Volatile Organic Compounds - J. E. Williams; P. F. J. van Velthoven; C. A. M. Brenninkmeijer (Atmospheric Chemistry and Physics, 2013)
The emission of organic compounds from biogenic processes acts as an important source of trace gases in remote regions away from urban conurbations, and is likely to become more important in future decades due to the further mitigation of anthropogenic emissions that affect air quality and climate forcing. In this study we examine the contribution of biogenic volatile organic compounds (BVOCs) towards global tropospheric composition using the global 3-D chemistry transport model TM5 and the recently developed modified CB05 chemical mechanism. By comparing regional BVOC emission estimates we show that biogenic processes act as dominant sources for many regions and exhibit a large variability in the annually and seasonally integrated emission fluxes. By performing sensitivity studies we find that the contribution of BVOC species containing between 1 to 3 carbon atoms has an impact on the resident mixing ratios of tropospheric O3 and CO, accounting for ~2.5% and ~10.8% of the simulated global distribution, respectively. This is approximately a third of the cumulative effect introduced by isoprene and the monoterpenes. By examining an ensemble of 3-D global chemistry transport simulations which adopt different global BVOC emission inventories we determine the associated uncertainty introduced towards simulating the composition of the troposphere for the year 2000. By comparing the model ensemble values against a composite of atmospheric measurements we show that the effects on tropospheric O3 are limited to the lower troposphere (with an uncertainty between −2% to 10%), whereas that for tropospheric CO extends up to the upper troposphere (with an uncertainty of between 10 to 45%). Comparing the mixing ratios for low molecular weight alkenes in TM5 against surface measurements taken in Europe implies that the cumulative emission estimates are too low, regardless of the chosen BVOC inventory. This variability in the global distribution of CO due to BVOC emissions introduces an associated uncertainty in the tropospheric CO burden of 11.4%, which impacts strongly on the oxidative capacity of the troposphere, introducing an uncertainty in the atmospheric lifetime of the greenhouse gas CH4 of ~3.3%. This study thus identifies the necessity of placing further constraints on non-CH4 global biogenic emission estimates in large-scale global atmospheric chemistry models.